1997
DOI: 10.1007/s002689900185
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Low‐Molecular‐Weight Heparin and Standard Unfractionated Heparin for Prophylaxis of Postoperative Venous Thromboembolism: European Multicenter Trial

Abstract: A randomized, double-blind multicenter trial was performed to compare the safety and efficacy of a new low-molecular-weight heparin (LMWH) (LU 47311, Clivarine) and standard unfractionated heparin for the prophylaxis of postoperative venous thromboembolism. Altogether 1351 patients scheduled to undergo abdominal surgery were included. Main outcome measures included the incidence of thromboembolic events (deep vein thrombosis, pulmonary embolism, or both) and bleeding complications, including wound hematoma. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…7,9 In contrast, there is a large body of evidence that therapeutic levels were reached faster and less monitoring was necessary in patients receiving low-molecular-weight heparin for anti-coagulation. 14,22,[31][32][33][34][35][36] In order to achieve optimal therapeutic levels, dosing of low-molecular-weight heparin needs to be adjusted to age and weight of children since dosing guidelines for adult patients cannot be transferred to children. 3,8,17,20 There were no serious complications including stroke, thrombotic events, or significant bleeding requiring intervention or causing permanent disability in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,9 In contrast, there is a large body of evidence that therapeutic levels were reached faster and less monitoring was necessary in patients receiving low-molecular-weight heparin for anti-coagulation. 14,22,[31][32][33][34][35][36] In order to achieve optimal therapeutic levels, dosing of low-molecular-weight heparin needs to be adjusted to age and weight of children since dosing guidelines for adult patients cannot be transferred to children. 3,8,17,20 There were no serious complications including stroke, thrombotic events, or significant bleeding requiring intervention or causing permanent disability in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar low rates of thrombotic 6,20,37 or bleeding 4,38,39 complications are reported in other studies investigating the use of low-molecular-weight heparin in the children for different indications. 18,33,[40][41][42] Superiority in efficacy, safety, and costs of low-molecular-weight heparin therapy compared with continuous-infusion unfractionated heparin for initiation of anti-coagulation after mechanical prosthetic valve implantation has been shown in adults. 43 Injection pain and anxiety pose additional physical and psychological stress on complex CHD children requiring numerous hospitalisations and interventions during early life and childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the occurrence of spinal epidural hematoma when using enoxaparin with epidural or spinal anesthesia was reported [20], but enoxaparin has a reduced risk of heparin-induced thrombocytopenia and hemorrhagic complications, severe bleeding, or wound hematomas compared with LDUH in large RCTs [21, 22]. Because our data from hematological examinations and clinical observations indicate that coagulability was not excessively affected by enoxaparin, we propose that this treatment is safe and efficacious without the need for laboratory monitoring of patients when appropriately used.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have found LMWH to be effective as UH in the prevention of DVT, but in view of its more convenient way of administration and overall risk benefit ratio, they advocated that LMWHs might be preferred over UH for DVT prophylaxis. [151920]…”
Section: Discussionmentioning
confidence: 99%